Pengaruh Ukuran Perusahaan, Leverage, Corporate Governance, Dan Profitabilitas Terhadap Manajemen Laba - Marina Tanudjaja, Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2022)
The objective of this study was to obtain an empirical evidence about the effect of firms’ size, leverage, institutional ownership, and profitability on earnings management in manufacturing companies which listed in Indonesia Stock Exchange on 2017-2019. Sample was selected using purposive sampling amounted to 74 manufacturing companies that met the criteria. Data processing techniques used multiple regression analysis that helped with Eviews 11 program. The results showed that firms’ size, leverage, and institutional ownership had no effect on earnings management, but profitability had positive effect on earnings management. The implication of this research was to provide information for companies about earnings management so the companies can minimize the possibility of earnings management and provide knowledge about earnings management for academics and future researchers.